Examining the changing demand for orthotic service provision from routinely collected digital patient data: A national retrospective descriptive study across three clinics in Cambodia - Charlotte Spurway; Alex Dickinson; Lucy Gates; Cheryl Metcalf; Sisary Kheng; Carson Harte; Bunthoeun Sam; Sam Simpson; Amos Channon (PLoS ONE, 2025)
Available data on the demand for orthotic services is limited, especially in low- and middle-income countries, yet the development and delivery of services relies on this information. In this study, routinely collected digital patient records are used to provide insights into orthotic service users from three Cambodian physical rehabilitation centres. Analysis of the digital patient records from 1998–2019 investigated trends by sex, clinic, reason for orthosis use, orthotic type, and age. The analysis showed that the characteristics of service users and the provision of orthotics have changed over time. The predominant reason for orthosis use prior to 2006 was polio, whereas in 2019 it was cerebral palsy. Ankle Foot Orthoses (AFOs) are the most common type of orthosis provided; however, key differences have been found between type of orthosis and age which suggests older individuals have different experiences of physical rehabilitation compared to younger age groups. Longitudinal trends indicate a substantial reduction in orthotics appointments which may be associated with change in service delivery and changing service user characteristics. The study has illustrated the insights which can be derived from digital patient records into the demand for orthotics services over two decades and demonstrates the need for targeted resources and planning for the provision of services.